Loudness encoding at the auditory nerve - Sagi, E.; Norwich, K.H.; Kunov, H. (Canadian Acoustics, 2001)
Using a method of magnitude estimation, human participants were required to quantify the loudness of a stimulus tone relative to a reference tone of some fixed level and frequency (or frequencies). After all stimulus tones were presented, the assigned values were normalized such that the reference tone was given a value of 1 `sone’. The obtained data indicates that in every auditory nerver fiber, the loudness becomes encoded in the error intrinsic to the fiber as it samples the sound level of the stimulus one.